Epidemiological Profile of HIV among Elderly in Brazil from 2019 to 2023 - , Camila Carvalho Do Vale; , Bruna Rafaela Da Silva Sousa; , Felipe Valino Dos Santos; , Geisa Adriele Silva Rodrigues; , Gizele De Oliveira Evangelista; , Gracileide Maia Corrêa; , Leidiane Almeida De Almeida; , Maylane Cristina BARROS Sousa; , Perla Katheleen Valente Corrêa; , Walter Lopes Neto (Archives of Current Research International, 2024)
Objective: To demonstrate the epidemiological profile of HIV cases in the elderly in Brazil from 2019 to 2023 Method: This is a descriptive epidemiological study, with a quantitative approach and a secondary base, from the SUS Information Technology Department (DATASUS), which is an open system that collects, processes and stores health data. Tables were used for analysis. Results: The Southeast region of the country is the most affected and the Midwest region the least. Males are more prevalent with HIV/AIDS than females, and as for hierarchy, heterosexuals, homosexuals and bisexuals were the most prevalent cases. Considerations: The data pointed to the invisibility of the AIDS problem among the elderly. Health education for this population and greater inclusion of the elderly in government programs to combat STIs, as well as quality public policies aimed at this public, are essential.